DIAGNOSIS OF STRESSED STATES IN THE LITHOSPHERE OF THE BAIKAL RIFT SYSTEM - Klyuchevskii A.V.; Klyuchevskaya A.A. (My University, 2007)
The results of investigation of the structure and dynamics of stresses at the modern (instrumental) stage of the evolution of the lithosphere in the Baikal Rift System (BRS) are presented. The application of the theoretical methods of nonlinear dynamic systems for diagnosis of the stressed states allowed us to formulate the concept of the complex stressed state of the BRS lithosphere. In this concept, the time distribution of large earthquakes is explained by bifurcations (catastrophes) of stresses. The analysis of the results obtained points to possibilities of a catastrophe of stresses in the BRS lithosphere in the next few years and the consequent realization of large earthquakes with magnitude M ≈ 7. A model of triple equilibrium bifurcation is suggested for the evolution of stresses in the BRS lithosphere.